2018
DOI: 10.3390/su10010093
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Architectural Heritage Management Implications for Tourism: The Case of Portugal

Abstract: Abstract:The aims of this study are manifold. First, to investigate the potentials of architectural heritage in the context of tourism destination development, as well as examine public sector policies and make plans toward the preservation of these resources. Secondly, to appraise the outcome of preservation and its implications for tourism. The study is an effort to explore and understand the interrelationships between tourism and architectural heritage sites through tourist image and perception. For the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 63 publications
1
19
0
1
Order By: Relevance
“…Architectural heritage resources are the most attractive to visitors [38], and several studies focused on how to rank heritage building conversion through experts' decision-making with multiple criteria [39,40]. This study indicated that heritage architecture, decoration, and style attracted visitors, though history and culture, cultural atmosphere, and well-preserved heritage were also important attractors.…”
Section: Theoretical Support For the Framework: Reuse Environmentmentioning
confidence: 97%
“…Architectural heritage resources are the most attractive to visitors [38], and several studies focused on how to rank heritage building conversion through experts' decision-making with multiple criteria [39,40]. This study indicated that heritage architecture, decoration, and style attracted visitors, though history and culture, cultural atmosphere, and well-preserved heritage were also important attractors.…”
Section: Theoretical Support For the Framework: Reuse Environmentmentioning
confidence: 97%
“…One group of authors dealt with vernacular architecture, examining traditional materials, traditional culture, patterns, and habits of construction [54,55]. A certain number of studies is dedicated to the formation of new cultural routes or inclusion of a facility in defined ones [56] while promoting facilities and culture through tourism development [57,58]. Some researchers have addressed the improvement of architectural heritage in terms of energy retrofitting [59,60].…”
Section: Theoretical Background 21 Architectural Heritage In Smart mentioning
confidence: 99%
“…While preparing these plans, protection of social and cultural structure of the region should not be neglected. Damaging the socio-cultural structure and historical buildings in the region will also give harm to tourism because, according to some studies, most tourists think that architectural heritage sources are the most attractive sites in the places they visit [20]. This means that a tourist visiting to a certain location wants to see the traditional and historical architecture in that area.…”
Section: Discussionmentioning
confidence: 99%